Childhood in Communist Literary Utopias of the First Half of the Twentieth Century - Witczak, Patryk (Porównania, 2023)
At the beginning of the twentieth century in Russia, with the rise in popularity of communist ideas and revolutionary tendencies, utopian works began to be written more frequently, in which visions of an ideal social order were spun. One of the problems addressed in literary utopias of this period was to propose a new concept of childhood. In the article, on the example of three novels: The Red Star by Alexander Bogdanov, The Coming World 1923–2123 by Yakov Okunev, and The State of the Happy by Jan Lari, it is shown how utopians imagined the place of the child in communist society. Three issues, related to the concept of childhood, were considered: family relations, concepts of upbringing, child infrastructure. The whole was set in the context of pedagogical concepts of the time.